Opioid modulation of intrinsically photosensitive retinal ganglion cells - Cleymaet, Allison Marie, author; Powell, Cynthia, advisor; Vigh, Jozsef, advisor; de Linde Henriksen, Michala, committee member; Hentges, Shane, committee member (Colorado State University. Libraries, 2019)
Widespread opioid use and abuse has resulted in an opioid epidemic in the United States and worldwide. Among several adverse effects of this drug class, opioids disrupt the sleep/wake cycle. While sleep induction and regulation is complex, and opioid receptors are known to be located in central sleep regulatory nuclei, it has not been specifically studied if opioids affect photoentrainment of circadian rhythm and thus the sleep/wake cycle. Intrinsically photosensitive retinal ganglion cells (ipRGCs) are the exclusive conduits for non-image forming visual functions, such as the aforementioned photoentrainment of systemic circadian rhythms, including the drive to sleep, and the pupillary light reflex (PLR). Systemically applied opioids cross the tight blood/retina barrier and thereby might alter the activity of retinal neurons. It has been recently shown that ipRGCs express μ-opioid receptors (MORs) and exogenously applied opioids inhibit the firing of ipRGCs. The current work aimed to identify the mechanism by which opioids inhibit ipRGC firing as well as downstream behavioral consequence of such inhibition at the organism level, specifically as manifested by modulation of PLR. Through the use of transgenic mice, electrophysiology including multi-electrode array recordings and patch clamp in whole and dissociated retinas, and immunohistochemistry, we have documented the following: (1) In the rodent retina M1-M3 types of intrinsically photosensitive ganglion cells (ipRGCs) express μ-opioid receptors (MORs). (2) Light-evoked firing of ipRGCs is attenuated by the MOR-specific agonist DAMGO in a dose-dependent manner. (3) MOR activation reduces ipRGC excitability by modulating IK and reducing the amplitude of non-inactivating ICa. Additionally, we explored the effect of modulation of ipRGC signaling via MORs on the murine PLR using transgenic mice and pupillometry. Our main findings were: (1) In WT mice but not in systemic μ-opioid receptor knockout mice (MKO) or mice in which μ-opioid receptors were selectively knocked out of ipRGCs alone (McKO), intraocular application of the MOR selective agonist DAMGO strongly inhibited rod/cone driven PLR and slowed melanopsin- driven PLR. (2) Intraocular application of a MOR selective antagonist CTAP enhanced rod/cone driven PLR in the dark-adapted retina and melanopsin driven PLR under photopic conditions in WT mice. In summary, these results identify both a novel site of action, MORs on ipRGCs, and a mechanistic description of a novel neural pathway by which exogenous and potentially endogenous opioids might alter light driven behavior, including the PLR, which may serve as a biomarker of systemic opioid effect.
Keywords: intrinsically photosensitive retinal ganglion cell; potassium; sleep; opioid; circadian; retina